Safety and Efficacy of Contemporary Drug-Eluting Stents in Patients With ST-Segment Elevation Myocardial Infarction and a High Ischemic Risk - Lee, Oh-Hyun; Kim, Yongcheol; Son, Nak-Hoon; Cho, Deok-Kyu; Kim, Jung-Sun; Kim, Byeong-Keuk; Choi, Donghoon; Hong, Myeong-Ki; Jeong, Myung Ho; Jang, Yangsoo (Frontiers in Cardiovascular Medicine, 2022)
Background: In patients with ST-elevation myocardial infarction (STEMI) with a high risk of ischemic events, the long-term safety and efficacy of drug-eluting stent (DES) are unclear. Methods: Based on the nationwide, multicenter, prospective registry, we selected 1,592 patients who underwent primary percutaneous coronary intervention (PCI) with everolimus-(EES) and zotarolimus-eluting stent (ZES) for STEMI with a high risk of an ischemic event. The occurrence of target lesion failure (TLF) for three years, defined as the composite of cardiac death, target vessel myocardial infarction (TV-MI), and ischemia-driven target lesion revascularization (ID-TLR), were evaluated. Results: The prevalence of high ischemic risk features was observed in 43.4% (2,744/6,325) of overall STEMI patients. Among them, a total of 1,078 and 514 patients were treated with EES and ZES, respectively. At three years, the risk of TLF was not significantly different between the two groups (p=0.93). In addition, the incidence of cardiac death, TV-MI, ID-TLR, and definite/probable stent thrombosis were also not different between the two groups. Moreover, elderly patients (age >75 years) and PCI for the left main disease were identified as independent predictors of TLF. Conclusion: Implantation of EES or ZES provided comparable long-term clinical outcomes in STEMI patients and high ischemic risks.